Design of An Automatic Fan Speed Controlling System Using Arduino UNO - M.Kumaran; I.Vikram; S.Kishore Kumar; R.Rajesh Kumar; S.Lokesh (International journal of intellectual advancements and research in engineering computations, 2018)
As we all know that we are slowly moving toward automation and automation is one of the trending topics. So, basically in this project we will be controlling fan speed with respect to the temperature of room or that of surrounding. The system will get the temperature from the temperature Sensor (LM35) and it will control the speed, of the according to the temperature, set by the user (i.e. if a person wants the fan to run at a particular RPM for a particular surrounding temperature we can do this via this project ). In this project, microcontroller forms the processing part, which firstly senses the temperature and the controller then compares the data with the set temperature. If the current temperature is greater than the set temperature, the controller turns ON the fan and the set speed will be proportional to the difference between the set temperature & the current temperature. If the current temperature is less than the set temperature, the fan will be turned OFF .The fan’s speed will change according to the temperature of the room or surrounding.